Autofluorescence imaging videobronchoscopy in the detection of lung cancer: from research tool to everyday procedure. (March 2011) - Zaric, Bojan; Perin, Branislav; Becker, Heinrich D; Herth, Felix FJF; Eberhardt, Ralf; Djuric, Mirna; Djuric, Dejan; Matijasevic, Jovan; Kopitovic, Ivan; Stanic, Jelena
Autofluorescence imaging videobronchoscopy (AFI) is one of the new systems of autofluorescence bronchoscopy designed for thorough examination of bronchial mucosa. The integration of autofluorescence and videobronchoscopy provides clear images of normal and pathologically altered bronchial mucosa. Major indications for AFI include evaluation of early-stage lung cancer and detection of precancerous lesions. However, in recent years, the indications for AFI are widening, and this tool might find its place in routine daily bronchoscopic practice. With new indications for AFI, such as evaluation of tumor extension or follow-up after surgical resection, this tool might be more often used by bronchoscopists. A sharp learning curve and clear distinction between healthy and pathologically altered mucosa make this technology acceptable for young and inexperienced bronchoscopists. One of the major disadvantages of AFI is low specificity in the detection of premalignant lesions and early-stage lung cancer. This disadvantage could be overcome with the appearance of new and improved technologies in autofluorescence, such as the addition of backscattered light analysis, ultraviolet spectra, fluorescence-reflectance or dual digital systems. Quantitative image analysis is also one of the ways to improve objectivity and minimize observer errors. However, one of the most appropriate solutions would be the addition of AFI to narrow band imaging, and merging the two technologies into one videobronchoscope.